Pelatihan Pembuatan Insectarium bagi Guru MTs. Dharut Tayyibin Batu Jai Kabupaten Lombok Tengah - Efendi, Ismail; Safnowandi, Safnowandi; Mursali, Saidil; Sabrun, Sabrun (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2022)
Efforts to improve the quality of science learning require various breakthroughs, both in curriculum development, learning innovation, learning media, and fulfilling educational facilities and infrastructure. To improve student achievement, teachers are required to make learning more innovative which encourages students to learn optimally both in independent learning and in classroom learning. In order for learning to be more optimal, it is also necessary that learning media must be effective and selective in accordance with the subjects taught in improving student achievement. Learning media is one of the important components in learning. Media is a tool to understand the concept or subject matter. Biology is a part of science which contains scientific concepts and develops science process skills. Science process skills can be possessed by students through direct observation of objects that involve various student activities in the classroom and outside the classroom. Today, the implementation of the science learning process, especially biology with the approach of science process skills and the use of learning media is still not optimal. There are still few teachers who want to develop science process skills in learning biology. Likewise, there are still teachers who are less creative in using learning media for various reasons, such as the availability of tools and practicum materials, limited funds, time and others. To find alternative solutions to the problem solving above, training on making an insectarium was held for Mts teachers. With the aim of training teachers to make a biology insectarium which is very important in supporting the implementation of biology practicum in schools. The target audience for this service are the teachers of Mts. Dharut Thayyibin Batu Jai, Central Lombok Regency. From the evaluation results, the results and benefits of this service activity include improving the skills of Mts teachers. in making a biology insectarium as a medium for learning biology. This service activity went smoothly, because of various supporters, especially the participation of participants who were quite enthusiastic and actively participated in this training activity. This training activity should be carried out on a broader target and the material can be developed in the manufacture of various types of Biological insectariums. Thus, it is hoped that in the future it will be able to help biology teachers in developing science learning media, so that the quality of science learning can be further improved.